EFFECTS OF CLIMATE CHANGE ON RICE PRODUCTION IN THE TROPICAL HUMID CLIMATE OF KERALA, INDIA - S. A. SASEENDRAN K. K. SINGH, L. S. RATHORE, S. V. SINGH and S. K. SINHA (Climatic Change 44: 495-514, 2000, 2000)
The CERES-Rice v3. crop simulation model, calibrated and validated for its suitability to simulate rice production in the tropical humid climate Kerala State of India, is used for analysing the effect of climate change on rice productivity in the state. The plausible climate change scenario for the Indian subcontinent as expected by the middle of the next century, taking into account the projected emissions of greenhouse gases and sulphate aerosols, in a coupled atmosphere-ocean model experiment performed at Deutsches Klimarechenzentrum, Germany, is adopted for the study. The adopted scenario represented an increase in monsoon seasonal mean surface temperature of the order of about 1.5 C, and an increase in rainfall of the order of 2 mm per day, over the state of Kerala in the decade 2040-2049 with respect to the 1980s. The IPCC Business-as-usual scenario projection of plant usable concentration of CO2 about 460 PPM by the middle of the next century are also used in the crop model simulation. On an average over the state with the climate change scenario studied, the rice maturity period is projected to shorten by 8 per cent and yield increase by 12 per cent. When temperature elevations only are taken into consideration, the crop simulations show a decrease of 8 per cent in crop maturity period and 6 per cent in yield. This shows that the increase in yield due to fertilisation effect of elevated CO2 and increased rainfall over the state as projected in the climate change scenario nearly makes up for the negative impact on rice yield due to temperature rise. The sensitivity experiments of the rice model to CO2 concentration changes indicated that over the state, an increase in CO2 concentration leads to yield increase due to its fertilisation effect and also enhance the water use efficiency of the paddy. The temperature sensitivity experiments have shown that for a positive change in temperature up to 5 C, there is a continuous decline in the yield. For every one degree increment the decline in yield is about 6 per cent Also, in another experiment it is observed that the physiological effect of ambient CO2 at 425 ppm concentration compensated for the yield losses due to increase in temperature up to 2 C. Rainfall sensitivity experiments have shown that increase in rice yield due to increase in rainfall above the observed values is near exponential. But decrease in rainfall results in yield loss at a constant rate of about 8 per cent per 2 mm/day, up to about 16 mm/day.